Prospects for off-label use of propranolol for the treatment of infantile hemangioma in children - Surzhykov, I.O.; Bevz , O.V.; Goncharuk, V.A.; Kryvanych, O.V.; Bevz , N.Y.; Georgiyants , V.A. (Medicni Perspektivi, 2025)
Infantile hemangiomas are the most common benign vascular tumors in infants, with a detection rate of 2-5% in newborns, while among premature infants their incidence reaches 23%. These tumors can vary greatly in size and location, sometimes causing serious complications such as visual, respiratory or bleeding disorders, which significantly impair the quality of life of patients and can lead to long-term consequences. Propranolol in the form of an oral solution has been approved as a first-line treatment for infantile hemangiomas, it has vasoconstrictor and antiangiogenic effects and promotes the induction of apoptosis of tumor endothelial cells, resulting in a significant reduction in hemangioma size and improvement in patient condition. Despite the high incidence of the disease, there are no standardized propranolol medicines for pediatric patients in Ukraine, which greatly complicates treatment and forces doctors to use off-label drugs. This creates risks associated with improper dosage, variability in the concentration of the active ingredient, and possible side effects. The purpose of the study is to analyze the scientific literature on the efficacy and safety of propranolol in the treatment of infantile hemangiomas, as well as to justify the need to develop new dosage forms for pediatrics. To achieve this goal, we analyzed scientific articles, clinical trial data, and the legislative framework, including international guidelines and treatment protocols. The study used methods of analysis, information systematization and genera¬lization.The results of the study show that propranolol is highly effective in the treatment of hemangiomas. Its therapeutic effect is explained by vasoconstrictor, antiangiogenic effects and induction of apoptosis of tumor endothelial cells. According to clinical trials, the standard treatment regimen involves the use of propranolol at a dose of 2-3 mg/kg of body weight per day for six months, which helps to reduce tumor size, low the possibility of complications and improve the quality of life of patients. The development of new, standardized pharmaceutical products for children with propranolol will increase the effectiveness of treatment and minimize side effects, making this issue relevant for both clinical practice and the pharmaceutical industry.